Pediatric cancer outcomes after the implementation of a residential hostel in Tanzania. Issue 10 (20th May 2022) - Morgan, Austin; Watt, Melissa; Zullig, Leah; Sued, Hillary; Schroeder, Kristin
Abstract: Background: A large survival disparity exists for pediatric cancer patients in low‐ and middle‐income countries compared with high‐income countries. A variety of factors contribute to this gap, including late‐stage disease at presentation, high rates of abandonment of care, and lack of supportive care infrastructure. A residential hostel was established in Mwanza, Tanzania, to reduce barriers to accessing and maintaining care among patients being treated for childhood cancer at a regional referral hospital. This study examines the effect of the hostel on one‐year survival and treatment abandonment for children diagnosed with cancer. Methods: Medical records were retrospectively reviewed for all patients presenting from May 2017 to April 2018, following the establishment of a pediatric cancer hostel at the referral hospital. Active follow‐up was used to confirm survival data. Results: There were 149 patients who presented to the referral hospital during the study period with 130 eligible for evaluation. A total of 34% ( n  = 44) used the hostel services and 66% did not use the hostel ( n  = 86). Patients who used the hostel did not significantly differ by age, sex, or diagnosis compared with patients who did not use the hostel. Patients who used the hostel had lower treatment abandonment (27% vs 37%) and higher one‐year overall survival (47% vs 37%) compared with patients who did not use the hostel. Conclusion: Our findings suggest key supportive programs such as a family hostel may be beneficial for patients with childhood cancer and can improve pediatric cancer treatment outcomes in LMICs.